2019
DOI: 10.1111/1467-923x.12737
|View full text |Cite
|
Sign up to set email alerts
|

Grey Power: Towards a Political Economy of Older Voters in the UK

Abstract: The impact of age on voting behaviour and political outcomes has become an issue of increasing interest, particularly in the UK. Age divides in voter turnout and political preferences have led to claims that age is the ‘new class’. In this article, we contrast existing ‘cultural backlash’ and political economy explanations of the age divide in politics, and challenge the view that older people are predominantly ‘left behind’, culturally or economically. We show that older people have distinct material interest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 10 publications
(15 reference statements)
1
13
0
1
Order By: Relevance
“…Birleşik Krallık'taki yaşlı politikalarına dair alanyazında, yaşlıların oy verme davranışları (Chrisp and Pearce, 2019), politika bağlamında yaşlanma ve toplumsal cinsiyet (Carney, 2018), ülkenin yaşlanma bağlamında sosyal politika ihtiyacı (Walker, 2018), yaşlılık, mesleki güç ve sosyal politika ilişkisi (Powell, 2001), yaşlılara yönelik hizmetlerde sosyal ve siyasi etkiler (Qureshi, 2002), yaşlanma ve sağlık bakımı harcamaları (Gusmano and Allin, 2014), uzaktan bakım teknolojileri, yaşlılar ve sosyal güvenlik krizi (Eccles, 2021) gibi farklı konular özelinde hazırlanmış çalışmalar bulunmaktadır. Dikkat edileceği üzere, bu çalışmalar siyasi partilerin yaşlılara yaklaşımlarını içermemektedir.…”
Section: Alanyazın Bilgisiunclassified
“…Birleşik Krallık'taki yaşlı politikalarına dair alanyazında, yaşlıların oy verme davranışları (Chrisp and Pearce, 2019), politika bağlamında yaşlanma ve toplumsal cinsiyet (Carney, 2018), ülkenin yaşlanma bağlamında sosyal politika ihtiyacı (Walker, 2018), yaşlılık, mesleki güç ve sosyal politika ilişkisi (Powell, 2001), yaşlılara yönelik hizmetlerde sosyal ve siyasi etkiler (Qureshi, 2002), yaşlanma ve sağlık bakımı harcamaları (Gusmano and Allin, 2014), uzaktan bakım teknolojileri, yaşlılar ve sosyal güvenlik krizi (Eccles, 2021) gibi farklı konular özelinde hazırlanmış çalışmalar bulunmaktadır. Dikkat edileceği üzere, bu çalışmalar siyasi partilerin yaşlılara yaklaşımlarını içermemektedir.…”
Section: Alanyazın Bilgisiunclassified
“…It was particularly important that the critical electoral constituency of older voters was not expected to shoulder any substantial costs of the reforms, save for workers approaching retirement in the years running up to the extension of the state pension age. In the United Kingdom, over 65 year olds have much higher turnout rates at elections than the young and middle aged, and age has become a central political cleavage (Chrisp and Pearce, 2019;Tilley and Evans, 2017). Political parties therefore had an interest in promoting the improvements to older voters' pensions, while avoiding blame for retrenchment that would impinge on their entitlements, as the new politics of the welfare state literature would predict (Pierson, 1996(Pierson, , 2001.…”
Section: Institutional Context Ideas and Political Agencymentioning
confidence: 99%
“…Future costs were controlled by accelerating the timetable for increases in the state pension age. More widely, cuts in social security spending in the period 2010–2015 were concentrated on the working age population; the electorally critical retired population saw its benefits protected (Chrisp and Pearce, 2019). The staged implementation of the reforms, and the careful sequencing of the costs of auto-enrolment and increases in the state pension age, combined with increases in the BSP, ensured that older voters did not mobilise in opposition to them.…”
Section: Temporality and Political Agencymentioning
confidence: 99%
“…Plutzer ( 2002 ) suggested that electoral behavior is habitual, as well as developmental, meaning that factors prone to change over a person’s life may shape their voting practices. Discrepancies in turnout could be explained by older voters typically having an increased stake in economic issues, including social security and home ownership, in addition to the fact that older adults tend to embrace value-based justifications for their preferences (Chrisp & Pearce, 2019 ). Young adults are generally labeled as apathetic or avoiding civic duties, but unconventional means of action, such as social media engagement and volunteering, have indicated that young voters may be motivated, but do not use traditional modes of participation as frequently as older adults (Shea, 2015 ).…”
Section: Introductionmentioning
confidence: 99%